Estigmatización social y acceso a la justicia: efectos de criminalización de consumidores en Riobamba tras eliminar la tabla de umbrales. - Ganán Paucar, Oscar Ramiro (2026)
The present study, entitled “Social Stigmatization and Access to Justice: Effects of the Criminalization of Consumers of Controlled Substances in Riobamba after the Elimination of the Threshold Table”, aimed to assess how social stigma expressed through the prosecution of substance consumers affects access to justice in Riobamba following the repeal of the threshold table. The research was developed within the framework of Critical Legal Studies, Sociology of Law, and the Human Rights perspective. Its main purpose was to determine whether consumers of controlled substances effectively access the justice system. A mixed methodological design was adopted, combining legal analysis, inductive reasoning, and dogmatic-normative approaches. Data was collected through semi-structured interviews with four specialized prosecutors and structured surveys administered to twenty-five incarcerated individuals. The findings reveal that, although the constitutional framework provides for adequate protection of rights, structural barriers persist that hinder access to justice. The elimination of the threshold table has increased judicial discretion and punitive practices. Judicial actors tend to adopt moralizing criteria and disregard restorative justice or health-oriented approaches. This scenario reinforces stigmatization, marginalizes consumers of controlled substances from judicial processes, and contradicts both national and international human rights standards. The study concludes that legal reforms, judicial training, and public policies grounded in health are urgently needed.